2022
DOI: 10.1183/20734735.0171-2021
|View full text |Cite
|
Sign up to set email alerts
|

Beyond antibiotics: recent developments in the diagnosis and management of nontuberculous mycobacterial infection

Abstract: Nontuberculous mycobacteria (NTM) pulmonary disease represents a significant clinical challenge with suboptimal therapy and increasing prevalence globally. Although clinical practice guidelines seek to standardise the approach to diagnosis and treatment of NTM disease, a lack of robust evidence limits their utility and significant variability exists in clinical practice. Here we walk through some novel approaches in diagnosis and therapy that are under development to tackle a disease where traditional strategi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 99 publications
0
3
0
Order By: Relevance
“…It is noteworthy that the resistance of M fortuitum strains varies geographically, and the choice of antibiotics should be based on local antimicrobial susceptibility data. A study by Zheng et al [13] has shown that in China, the resistance of M fortuitum strain is lower to moxifloxacin and amikacin, but significantly higher to macrolides, compared to that reported in the studies by Shahraki et al, and Gleeson et al [5,14] This might be related to the frequent use of macrolides by Chinese doctors to treat respiratory mycoplasma infections, leading to increased exposure to the drug. [15,16]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is noteworthy that the resistance of M fortuitum strains varies geographically, and the choice of antibiotics should be based on local antimicrobial susceptibility data. A study by Zheng et al [13] has shown that in China, the resistance of M fortuitum strain is lower to moxifloxacin and amikacin, but significantly higher to macrolides, compared to that reported in the studies by Shahraki et al, and Gleeson et al [5,14] This might be related to the frequent use of macrolides by Chinese doctors to treat respiratory mycoplasma infections, leading to increased exposure to the drug. [15,16]…”
Section: Discussionmentioning
confidence: 99%
“…NTMs are opportunistic pathogen that can cause various infections, including skin and soft tissue infections, pulmonary infections, and disseminated infections in immunocompromised individuals. [1][2][3][4][5] Skin and soft tissue infections caused by NTMs often occur after surgery, trauma, or injection. [6] As a subgroup of NTMs, M fortuitum is characterized by its weak pathogenicity, non-toxin production, high tolerance and rapid growth compared to other NTM members.…”
Section: Introductionmentioning
confidence: 99%
“…Treatment often involves harsh and protracted effects, potentially leading to patient discontinuation or non-adherence [57]. On average, culture conversion (two consecutive pathogen free sputum cultures) rates hover around 60-70%, with recurrence rates reaching 50% [58]. Hence, it is imperative to optimize treatment strategies and explore novel, effective, and well-tolerated medications [59].…”
Section: Nontuberculous Mycobacteria: Environmentally Versatile Oppor...mentioning
confidence: 99%